GUEPINIOPSIS ORESBIA, A NEW WOOD DESTROYING BASIDIOMYCETE - RANGKUTI, D.; RIFAI, MIEN A. (Research Center for Biology, 1975)
A new dacrymycetaceous fungus is described and illustrated baaed on specimens found growing on Schima, Vaccinium, Casuarina and other decayed wood in mountain areas in Java.